Association of Socio-Demographic Factors with Physical Activity in Adolescents and Young Adults: Data from Ebans Study - De Moraes-Ferrari, G (Springer-Verlag Italia s.r.l., 2024)
Purpose: To describe the physical activity (PA) level and its association with socio-demographic factors in the Brazilian youth. Methods: We analyzed 476 individual participants of the Brazilian Study of Nutrition and Health (EBANS), using the age cutoff proposed by the World Health Organization to define the adolescence period. The International Physical Activity Questionnaire, was used to obtain PA data. Region, sex, age, socioeconomic level (SEL), education level, and type of occupation were used as socio-demographic factors. The multiple logistic regression stepwise was used for the associated factors. Results: 48% of adolescents and 53% of young adults did not meet the PA recommendations. For adolescents, sex (female OR 0.43; 95%CI 0.23–0.78), SEL (low OR 5.65; 95%CI 1.91–16.67) and type of occupation (student OR 2.07; 95%CI 1.04–4.12) were associated with PA recommendations meeting, and for adults only region (Northeast OR 0.24; 95%CI 0.06–0.97 and Midwest OR 0.16; 95%CI 0.03–0.89) and sex (female OR 0.47; 95%CI 0.25–0.87). Conclusions: The socio-demographic factors identified in this work may be considered in interventions aimed to increase the PA level in the Brazilian youth. The prevalence of individuals who did not meet the PA recommendations found in this study suggests an eminent need to foster sustainable public policies to increase the PA level in the population aged 15–24.9 years. Trial registration: ClinicalTrials.Gov NCT02226627. Retrospectively registered on August 27, 2014. © The Author(s), under exclusive licence to Springer-Verlag Italia S.r.l., part of Springer Nature 2024.